Studi Literatur: Penggunaan Media Sosial Sebagai Faktor Risiko Terjadinya Depresi - Ira Munirah (Yayasan Pendidikan Medika Indonesia, 2024)
Social media is an internet-based media that can be used as a means of communication and a source of information. As a result, the intensity of social media use is quite high among people. Unwise use of social media can cause a person to experience depression. Based on the Technology Acceptance Model (TAM) theory, perceived usefulness (PU) and perceived ease of use (PEU) can potentially affect the low or high intensity of social media use related to a person's level of depression. Depression is a mood disorder characterized by depressive affect, loss of interest or excitement, and loss of energy such as fatigue and decreased activity. The pathophysiology of depression occurs due to an imbalance of the neurotransmitters serotonin, norepinephrine and dopamine in the brain. The etiology of depression can be caused by a combination of factors, including biological, psychological, and social factors. Clinical manifestations of depression can be found in symptoms such as loss of interest and energy, reduced concentration, decreased self-confidence, feeling guilty or useless, pessimism, sleep disturbances and self-harm or suicidal thoughts. These conditions can be prevented by limiting use and doing positive activities. Management for depression therapy can be done with lifestyle changes, psychological therapy and medication. The purpose of writing a literature review is to examine more deeply the use of social media as a risk factor for depression.